Primary tuberculosis of the parotid gland: A forgotten diagnosis about a case!. Issue 5 (4th May 2021) - Benaissa, Elmostafa; Bahalou, Mohamed Habib; Safi, Yassine; Bssaibis, Fatna; Benlahlou, Yasssine; Chadli, Mariama; Maleb, Adil; Elouennass, Mostafa
Abstract: The diagnosis of tuberculosis must be made in the face of any cervical swelling, and the treatment is essentially medical. Abstract : The diagnosis of tuberculosis must be made in the face of any cervical swelling, and the treatment is essentially medical.